2013
DOI: 10.1111/tpj.12156
|View full text |Cite
|
Sign up to set email alerts
|

A variant of LEAFY reveals its capacity to stimulate meristem development by inducing RAX1

Abstract: SUMMARYIn indeterminate inflorescences, floral meristems develop on the flanks of the shoot apical meristem, at positions determined by auxin maxima. The floral identity of these meristems is conferred by a handful of genes called floral meristem identity genes, among which the LEAFY (LFY) transcription factor plays a prominent role. However, the molecular mechanism controlling the early emergence of floral meristems remains unknown. A body of evidence indicates that LFY may contribute to this developmental sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 74 publications
4
62
1
Order By: Relevance
“…Up to now, few transcription factors have been reported to directly regulate RAX genes. LEAFY was reported to bind to the promoter region of RAX1 directly (Chahtane et al, 2013). Our data suggested that RAX genes are very likely regulated by EXB1 directly for the following reasons.…”
Section: Discussionmentioning
confidence: 83%
“…Up to now, few transcription factors have been reported to directly regulate RAX genes. LEAFY was reported to bind to the promoter region of RAX1 directly (Chahtane et al, 2013). Our data suggested that RAX genes are very likely regulated by EXB1 directly for the following reasons.…”
Section: Discussionmentioning
confidence: 83%
“…This discrepancy has recently been reconciled by the finding that auxin promotes the expression of LEAFY (LFY), a key regulator of the floral transition, and that LFY feeds back to the auxin pathway (Li et al, 2013;Yamaguchi et al, 2013). LFY further activates the expression of RAX1 to promote inflorescence branching (Chahtane et al, 2013).…”
Section: Conservation and Divergence Of Hormonal Regulation Of Shoot mentioning
confidence: 94%
“…Interestingly, two separate mutation studies using the same amino acid substitutions in the dimerization interface obtained opposite results. 11,14 In our study, the amino acid sequences of the dimerization interfaces are not identical in the AtLFY and PpLFY1 proteins. Nevertheless, except for different interaction modes at position 312 in helix α3, the two LFY proteins have similar DNAbinding specificity (see Table 1).…”
Section: 3mentioning
confidence: 73%
“…In 2013, based on the crystallographic data of 2008, Chahtane et al generated a LFY allele that has an altered dimerization interface in vivo. 14 This study broke new ground by revealing a novel role for LFY in enabling meristem outgrowth. They confirmed the importance of LFY monomer− monomer contacts and tested the effect of the mutations at the dimerization interface on LFY DNA-binding specificity.…”
Section: Introductionmentioning
confidence: 95%